Maternal 'theories' and infant personality development - Noble, Rodney Sommerville. (The University of Edinburgh, 1984)
This "thesis "begins with a detailed theoretical analysis which is used to "build a framework to describe personality and personality development. The framework derives principally from the personality theory of George Kelly and the philosophical analysis of Thomas Kuhn. Kelly's theory of Personal Construct psychology is based on the image of man-as—scientist; Kuhn provides an account of thte nature and structure of science as a human endeavour. A simple version of a 'construct theory' - the psychological structure upon which the developing framework is based - is used to describe four major theoretical positions in personality research namely, the Psychometric, Behaviourist, Psychodynamic and Social Psycho¬ logical positions.

Specific exemplars of these positions are discussed. The parti¬ cular theories used were chosen for their contribution towards many of the issues raised in the thesis as well as exemplifying a particular approach.

Two issues, gender differences and birth—order effects are studied in depth (in Chapter 3) because they expose the dialectic incorporated in the person—situation construct forming part of the 'theory' used in Chapter 1. This aspect is explored by elaboration of both poles of the construct and a resolution in terms of a'superordinate synthesis' is proposed and supported. This synthesis is an integral part of the frame¬ work suggested and is exemplified by the method of exploring human meaning suggested by J.P. Sartre under the name of 'Existential Psychoanalysis'. Chapter 5 explores and elaborates the developmental aspects of the Personal Construct model and introduces the major practical concern of the thesis - the impact of mothers' 'theories' (i.e. construct theories) upon their children. Reasons for expecting these 'theories' to have an important influence upon children's personality development are advanced and the methods developed by the author for assessing maternal construing patterns are described. The results of applying these methods to a sample of volunteer mothers are described and discussed in terms of the adequacy of the methodology used. Conclusions are drawn concerning the development of more adequate measurement techniques and ways of extending and enriching the research presented in this thesis.